Elevated oxytocin receptor blood concentrations predict higher risk for, more, and earlier 24-month hospital readmissions after in-patient detoxification in males with alcohol use disorder - Mühle, Christiane; Mazza, Massimiliano; Weinland, Christian; Zimmermann, Claudia von; Bach, Patrick; Kiefer, Falk; Grinevich, Valéry; Zoicas, Iulia; Kornhuber, Johannes; Lenz, Bernd (International journal of molecular sciences, 2022)
Alcohol use disorder (AUD) is a major global mental health challenge. Knowledge concerning mechanisms underlying AUD and predictive biomarkers of AUD progression and relapse are insufficient. Recently, addiction research is focusing attention on the oxytocin system. However, to our knowledge, blood concentrations of the oxytocin receptor (OXTR) have not yet been studied in AUD. Here, in sex-separated analyses, OXTR serum concentrations were compared between early-abstinent in-patients with AUD (113 men, 87 women) and age-matched healthy controls (133 men, 107 women). The OXTR concentrations were correlated with sex hormone and oxytocin concentrations and alcohol-related hospital readmissions during a 24-month follow-up. In male patients with AUD, higher OXTR concentrations were found in those with an alcohol-related readmission than in those without (143%; p = 0.004), and they correlated with more prospective readmissions (ρ = 0.249; p = 0.008) and fewer days to the first readmission (ρ = −0.268; p = 0.004). In men and women, OXTR concentrations did not significantly differ between patients with AUD and controls. We found lower OXTR concentrations in smokers versus non-smokers in female patients (61%; p = 0.001) and controls (51%; p = 0.003). In controls, OXTR concentrations correlated with dihydrotestosterone (men, ρ = 0.189; p = 0.030) and testosterone concentrations (women, ρ = 0.281; p = 0.003). This clinical study provides novel insight into the role of serum OXTR levels in AUD. Future studies are encouraged to add to the available knowledge and investigate clinical implications of OXTR blood concentrations.
Dieser Artikel gehört zur Collection 21st anniversary of IJMS: Advances in molecular endocrinology and metabolism
Gesehen am 02.10.2023